ANALISIS NILAI TAMBAH PENGOLAHAN JAMUR TIRAM MENJADI JAMUR KRISPY PADA PETANI JAMUR DI KAMPUNG MELAYU KOTA BENGKULU - Afriani, Ririn (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Mushrooms are natural resources with great potential in the food and agribusiness sectors. Their high nutritional content, low fat, and variety of types make mushrooms highly valuable as a food ingredient. Additionally, mushrooms can be produced at relatively low costs, making them an attractive commodity for development in the agricultural sector. One increasingly popular processed product is crispy mushrooms.The purpose of this research is to analyze the value-added of crispy mushrooms. The research location was purposively determined in Kampung Melayu, Bengkulu City, considering that there is mushroom cultivation and processing of crispy mushrooms in that area. The sample used in this study consisted of farmers from "Mushroom House" who were purposively selected because they engage in mushroom cultivation and sell processed mushroom products. The research findings indicate that the value-added ratio is 62.12%, calculated by subtracting the output value from the raw material price of Rp.82,000. This means that every 1 kilogram of oyster mushrooms creates added value of Rp.82,000 per kilogram after being processed into crispy mushrooms. The profit obtained from the processing of these oyster mushrooms is Rp.69,200 per kilogram, with a profit margin of 52.42% of the output value.